Swarm Robot Communications in ROS 2: An Experimental Study - Castillo-Sánchez, José Borja; González-Parada, Eva; Cano-García, José Manuel (IEEE, 2024)
In recent decades, robots have become increasingly popular and accessible. New frameworks have emerged to develop and communicate robotic applications, with ROS 2 or Robot Operating System 2 entitled as the preferred choice. Our work presents a testbed and defines a methodology to evaluate the validity of ROS 2 middleware for enabling dependable wireless robot swarm communications. Wireless robot swarms are constrained by a number of factors, including their limited computational power and the fact that they communicate over wireless mediums. Wireless media are typically more susceptible to errors, exhibit higher latencies, or may be subject to outage zones. Consequently, this paper proposes an experimental approach using genuine robot-grade hardware and employing standard communication mechanisms, with the objective of achieving an optimal balance between messaging reliability and delay. A series of test cases were defined, each with distinct settings, including distance, bit coding, diffusion mechanism, and so forth. The results can be readily replicated with the publicly available code and scripts for tests and analysis. Our findings indicate a significant lack of optimisation with respect to ROS 2 wireless communications in swarm scenarios. To address this, we propose a series of recommendations for improving the efficiency of these communications.
MCIN/AEI/10.13039/501100011033 (Grant Number: TED2021-130456B-I00) EU “NextGenerationEU/PRTR” Program Malaga University Project (Grant Number: B4-2023-12)
Keywords: Robótica - Diseño y construcción; Autómatas; Swarm robots; Embedded systems; Network analysis; DDS; ROS 2